2021
DOI: 10.1002/mnfr.202100157
|View full text |Cite
|
Sign up to set email alerts
|

Betaine Delayed Muscle Loss by Attenuating Samtor Complex Inhibition for mTORC1 Signaling Via Increasing SAM Level

Abstract: Scope The muscle loss during aging results from the blunt of protein synthesis and poses threat to the elderly health. This study aims to investigate whether betaine affects muscle loss by improving protein synthesis. Methods and Results Male C57BL/6J mice are raised from age 12 or 15 months. Mice are fed with AIN‐93M diet without or with 2% w/v betaine in distilled water as control group or betaine intervention group (Bet), respectively. Betaine supplementation to mice demonstrates better body composition, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
8
1
Order By: Relevance
“…Moreover, betaine treatment increased the cross-sectional area of the quadricep muscle about 1.4-fold and 1.3-fold in 15- and 18-months mice, respectively. 23 Taken together, these data suggested that betaine supplementation promotes skeletal muscle differentiation and hypertrophy both in vitro and in vivo. However, in our setting, betaine had hypertrophic effect in myotubes treated with TNF-α only, showing a protective effect on inflammation-derived atrophy but not a net effect in control myotubes.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Moreover, betaine treatment increased the cross-sectional area of the quadricep muscle about 1.4-fold and 1.3-fold in 15- and 18-months mice, respectively. 23 Taken together, these data suggested that betaine supplementation promotes skeletal muscle differentiation and hypertrophy both in vitro and in vivo. However, in our setting, betaine had hypertrophic effect in myotubes treated with TNF-α only, showing a protective effect on inflammation-derived atrophy but not a net effect in control myotubes.…”
Section: Discussionmentioning
confidence: 82%
“…37 After 12 weeks intervention, mice treated with betaine displayed a 1.3- to 1.5-fold higher protein synthesis rate (measured by SUnSET method) than mice in age-matched control group. 23 Moreover, the same study showed that betaine increased muscle protein synthesis and hypertrophy in a time-dependent manner. 23 To treat myotubes, a concentration of 10 mM betaine has been chosen based on previous works performing dose-response on cell viability, proliferation, and differentiation of C2C12.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several functional BHMT variants have been identified in humans and are associated with increased risk for cancer and other diseases [ [64] , [65] , [66] , [67] ], however, no information is available on the metabolic phenotypes of humans carrying those variants. In mice, betaine supplementation delays muscle loss in an aging model [ 68 ], and more studies are needed to investigate if this happens in humans. In a meta-analysis of randomized controlled trials, betaine supplementation is associated with reduced body fat mass and body fat percentage; however, no changes on BMI were reported [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Body fat was lowered with betaine supplementation [32], so the effects of betaine on body mass may depend on the species, kidney function status, and/or high metabolic demand. Betaine may exert its effect on increasing body mass by increasing protein synthesis [33] and the cell proliferation rate in regulating the cellular response to hyperosmolarity [34].…”
Section: Discussionmentioning
confidence: 99%